Pyrimidine biosynthesis is not an essential function for Trypanosoma brucei bloodstream forms. - Juma A M Ali; Daniel N A Tagoe; Jane C Munday; Anne Donachie; Liam J Morrison; Harry P de Koning (PLoS ONE)
Background African trypanosomes are capable of both pyrimidine biosynthesis and salvage of preformed pyrimidines from the host, but it is unknown whether either process is essential to the parasite. Methodology/principal findings Pyrimidine requirements for growth were investigated using strictly pyrimidine-free media, with or without single added pyrimidine sources. Growth rates of wild-type bloodstream form Trypanosoma brucei brucei were unchanged in pyrimidine-free medium. The essentiality of the de novo pyrimidine biosynthesis pathway was studied by knocking out the PYR6-5 locus that produces a fusion product of orotate phosphoribosyltransferase (OPRT) and Orotidine Monophosphate Decarboxylase (OMPDCase). The pyrimidine auxotroph was dependent on a suitable extracellular pyrimidine source. Pyrimidine starvation was rapidly lethal and non-reversible, causing incomplete DNA content in new cells. The phenotype could be rescued by addition of uracil; supplementation with uridine, 2'deoxyuridine, and cytidine allowed a diminished growth rate and density. PYR6-5(-/-) trypanosomes were more sensitive to pyrimidine antimetabolites and displayed increased uracil transport rates and uridine phosphorylase activity. Pyrimidine auxotrophs were able to infect mice although the infection developed much more slowly than infection with the parental, prototrophic trypanosome line. Conclusions/significance Pyrimidine salvage was not an essential function for bloodstream T. b. brucei. However, trypanosomes lacking de novo pyrimidine biosynthesis are completely dependent on an extracellular pyrimidine source, strongly preferring uracil, and display reduced infectivity. As T. brucei are able to salvage sufficient pyrimidines from the host environment, the pyrimidine biosynthesis pathway is not a viable drug target, although any interruption of pyrimidine supply was lethal.